An in situ kinetic study of brass dezincification and corrosion. (1st March 2017) - Zhou, P.; Hutchison, M.J.; Erning, J.W.; Scully, J.R.; Ogle, K.
Abstract: The kinetics of the anodic dissolution of brass (CuZn42 and CuZn21Si3P) in synthetic tap water were investigated by atomic emission spectroelectrochemistry. Elemental Cu and Zn dissolution rates were measured in situ and in real time during galvanostatic dissolution. A complete mass/charge balance for the system yielded, as a function of applied current and a function of time, the quantity of Cu in the dezincification layer and the quantity of Cu and Zn in the oxide layer. In this way, a complete kinetic characterization of the fundamental chemical processes occurring during dezincification was realized for the first time. The oxide layer was composed primarily of Cu2 O as indicated by grazing incidence XRD and Raman analysis. The soluble Cu oxidation product was determined to be Cu(II) by a mass/charge balance. Zn was oxidized to soluble Zn(II) leaving behind a trivial amount of solid Zn corrosion product on the surface. The kinetic analysis depicts a two-stage dissolution process of dezincification: a first stage of a rapid growth of the dezincified layer and a second stage where the growth of dezincified layer was much slower. The Cu2 O layer grows continually during the exposure.